A Comparative study of intraoperative peritonsillar infiltration versus intravenous dexemedetomidine for perioperative analgesia in tonsillectomy - Lahane, Priya Vishwanath; Nandanvankar, Niteen. Khanderao; Pradeep, Meenakshi Sumadevi; Memon, Nazima Yusuf; Yennawar, Shridhar Devidas (Asian Journal of Medical Sciences, 2020)
Background: Tonsillectomy is one of the most common surgical procedures in population and post tonsillectomy pain affects analgesic consumption, hospital stay, oral intake and return to regular activity. Aims and Objectives: The purpose of the study was to compare peritonsillar infiltration and intravenous administration of dexmedetomidine for perioperative analgesia in tonsillectomy. Materials and Methods: This was a placebo-controlled study to compare peritonsillar infiltration and intravenous administration of dexmedetomidine in patients undergoing tonsillectomy. Ninety patients were included in this study on the basis of a predefined inclusion and exclusion criteria. These patients were divided in 3 groups on the basis of whether they received Peritonsillar dexmedetomidine, intravenous dexmedetomidine or intravenous normal saline. The groups were compared for post-operative pain, time to first request of rescue analgesia (duration of analgesia), post-operative sedation, analgesic requirement during first 24 hours and side effects. SSPS 21.0 was used for statistical analysis and p value less than 0.05 was taken as statistically significant. Results: Out of total 90 patients included in this study there was a female preponderance with a M: F ratio of 1:1.5. The mean age and ASA grades and mean duration of surgery of patients in all 3 groups were found to be comparable with no statistically significant difference in any of the groups (P>0.05). Preoperative mean systolic and diastolic blood pressures as well as mean arterial pressure and SPO2 was found to be comparable in all 3 groups. However intraoperative blood pressures (systolic, diastolic as well as mean arterial pressures) and SPO2 showed significant difference amongst the groups (P<0.05). Time to first request of rescue analgesia was found to be more in group - Dpt than group – Div and group – Pb which was highly statistically significant (p <0.0001).There was statistical significant difference in number of diclofenac injections consumed during first 24 hours between group – Dpt & group – Div and highly significant difference between group – Dpt & group – Pb, group – Div & group – Pb. Conclusion: Peritonsillar infiltration of dexmedetomidine is better alternative to intravenous dexmedetomidine in tonsillar surgeries.